POLA KEPEMIMPINAN KIYAI DALAM MENGEMBANGKAN PENDIDIKAN BERBASIS KARAKTER DI PONDOK PESANTREN AL MUNAWWIR KRAPYAK YOGYAKARTA - Isti Lailatul Amanah; Fandi Akhmad; Nurjannah; Tedi Wardani (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
The globalization era is developing at this time demands the existence of national cadres who have the quality of human resources as a whole, tough in facing all the challenges of the times. This can be realized in the support of a quality education system. Among Muslims themselves, Islamic boarding schools are referred to as examples of educational institutions that have advantages, both from the aspect of scientific tradition and morality. Islamic boarding schools are considered capable of instilling the character values of education in children so that the nation's cadres have full human resources. The research method that the author uses in this study is using qualitative research with a location in PP Al Munawwir Krapyak Yogyakarta, the results of this study are the leadership style applied by the Al Munawwir Krapyak Islamic boarding school, namely the democratic system, deliberation for consensus and also an authoritarian system. And in developing students' character education, namely by providing advice, habituation, exemplary (uswatun Hashanah), giving rewards and punishments to students.